Electronic structure effects in spatiotemporally resolved photoemission interferograms of copper surfaces - Ambrosio, M. J.; Thumm, U. (My University, 2017)
Attosecond photoelectron spectroscopy allows the observation of electronic processes on attosecond time scales (1as=10−18 s), as has been demonstrated in proof-of-principle experiments that probe the electronic dynamics in isolated atoms with unprecedented accuracy. Its recent expansion to solid targets is starting to allow the distinction of ultrafast collective electronic processes in matter with added spatial resolution, probing the electronic band structure and dielectric response in nanoplasmonically enhanced light-induced processes of relevance for photocatalysis, optoelectronics, and light harvesting. Based on a quantum-mechanical model for photoelectron emission by an attosecond pulse train from the d band of a Cu(111) surface into a delayed assisting laser pulse, we calculate two-pathway two-photon interferograms as functions of the photoelectron energy and pulse delay. Our results scrutinize the dependence of observable photoelectron interferograms on the electronic structure of and electron transport in the substrate and agree well with experimental spectra and semiclassical Monte Carlo simulations of Lucchini et al. [Phys. Rev. Lett. 115, 137401 (2015)].
Citation: Ambrosio, M. J., & Thumm, U. (2017). Electronic structure effects in spatiotemporally resolved photoemission interferograms of copper surfaces. Physical Review A, 96(5), 051403. https://doi.org/10.1103/PhysRevA.96.051403
Keywords: Atomic, Molecular & Optical; Metals; Photoemission; Surface adsorption